2015
DOI: 10.1209/0295-5075/112/17004
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic spin Hall effect in systems with striped spin-orbit coupling

Abstract: The Rashba spin-orbit coupling arising from structure inversion asymmetry couples spin and momentum degrees of freedom providing a suitable (and very intensively investigated) environment for spintronic effects and devices. Here we show that in the presence of strong disorder, nonhomogeneity in the spin-orbit coupling gives rise to a finite spin Hall conductivity in contrast with the corresponding case of a homogeneous linear spin-orbit coupling. In particular, we examine the inhomogeneity arising from a strip… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…As claimed in Refs. 33,34 , we here conclude that due to spin-flip processes along the lateral direction | C | < | Σ |, which results in a non-zero spin Hall conductance. A possible longer spin-relaxation time along the direction normal to the layer, as already experimentally evidenced in other types of confined Rashba system 35 may enhance the characteristic spin-diffusion length and size of SHE-ISHE compared to IEE in-plane effects.…”
Section: Figure 1 a Because Of Thementioning
confidence: 53%
“…As claimed in Refs. 33,34 , we here conclude that due to spin-flip processes along the lateral direction | C | < | Σ |, which results in a non-zero spin Hall conductance. A possible longer spin-relaxation time along the direction normal to the layer, as already experimentally evidenced in other types of confined Rashba system 35 may enhance the characteristic spin-diffusion length and size of SHE-ISHE compared to IEE in-plane effects.…”
Section: Figure 1 a Because Of Thementioning
confidence: 53%
“…On the theoretical side, Scopigno et al [6] suggested that the EPS in ST-LAO/STO results from a lateral confinement tendency of the MES to avoid a thermodynamically unstable state with negative compressibility. Other non-V O scenarios invoked formation of a Jahn-Teller polaronic phase [56], Rashba spin-orbit coupling [57,58], and even superconducting pairing interaction [58].…”
Section: Eps In St-lao/sto and Discussionmentioning
confidence: 99%
“…It is also worth to notice that the spiral state implies a breaking of translational invariance of the system along the longitudinal direction and hence a modulation at an effective level of the RSOC and hopping couplings. In this sense, it would be interesting to investigate if the presently studied system shows a spin Hall conductivity that remains robust against disorder as in a recently proposed model with modulated RSOC [50].…”
Section: Discussionmentioning
confidence: 99%